2019
DOI: 10.1080/15384047.2019.1670521
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq analysis of peripheral blood mononuclear cells reveals unique transcriptional signatures associated with radiotherapy response of nasopharyngeal carcinoma and prognosis of head and neck cancer

Abstract: Pan (2020) RNA-Seq analysis of peripheral blood mononuclear cells reveals unique transcriptional signatures associated with radiotherapy response of nasopharyngeal carcinoma and prognosis of head and neck cancer,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…It has been reported to be related to the clinical outcomes of acute lymphoblastic leukemia patients (42). Along with CHAC2, CLEC9A, and 8 other genes, JCHAIN was also found to be associated with survival in head and neck squamous cell carcinoma (43). Moreover, You reported that JCHAIN might exert a critical influence on resistance and tumorigenesis in Marek's disease (44).…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported to be related to the clinical outcomes of acute lymphoblastic leukemia patients (42). Along with CHAC2, CLEC9A, and 8 other genes, JCHAIN was also found to be associated with survival in head and neck squamous cell carcinoma (43). Moreover, You reported that JCHAIN might exert a critical influence on resistance and tumorigenesis in Marek's disease (44).…”
Section: Discussionmentioning
confidence: 96%
“…KLRB1 protein is expressed by NK cells and may be involved in the regulation of NK cell function. Previous studies shows that high expression of KLRB1 is closely related to the better prognosis of HNSCC patients [ 26 ]. CCL19, as the ligand of CCR7, induces several CCR7 activated pathways in metastatic HNSCC [ 27 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-574-5p, miR-9 and miR92a, which modulate the expression of MHC class I and interferon-regulated genes associated with NPC metastasis, could potentially be non-invasive blood-based biomarkers for metastasis prediction [ 132 , 133 ]. RNA sequencing of NPC patients’ peripheral blood mononuclear cells (PBMC) before and after RT has revealed 11 potential mRNA prognostic biomarkers for NPC for post-RT evaluation [ 160 ]. RNA_0000285 at homeodomain interacting protein kinase 3 (HIPK3) was observed in high level radio-resistance NPC patients and low radiosensitive NPC patients, thus showing its ability to predict NPC radiosensitivity [ 136 ].…”
Section: Npc Prognosis Biomarkersmentioning
confidence: 99%